Hemophagocytic lymphohistiocytosis (HLH) associated with scrub typhus: Report of 2 cases (Indian Journal of Case Reports, 2019)
Hemophagocytic Lymphohistiocytosis (HLH) is a fatal hyperinflammatory syndrome characterized by histiocytic proliferation along with hemophagocytosis. HLH can be primary (inherited) or secondary, to any severe infection, malignancy or rheumatological disease. HLH, though rare, has also been noted in association with scrub typhus which is an acute febrile illness resulting from the bite of infected larval form of mite (also known as chigger). We hereby describe two cases of HLH associated with rickettsial infection (Oriental tsutsugamushi) in a 36-year-old male and in a 10-year-old male child. The former presented with high-grade fever and pruritic macular rash over abdomen. While the latter was presented with fever and decreased urinary output at the time of admission.